Wpływ nauki na funkcjonowanie i rozwój systemu penitencjarnego w Polsce - Szymanowski, Teodor (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The study is an analysis of research and teaching issues related to the penitentiary system. Reflection in this area includes various disciplines of knowledge such as law, criminology, sociology, psychiatry, psychology, pedagogy (especially social rehabilita-tion), medical knowledge, protection and security strategies, economics and manage-ment. The author, from the perspective of the indicated disciplines, analyzes the recent development of executive law and assesses scientific research conducted in our country.
Keywords: system penitencjarny; nauczanie prawa karnego; badania empiryczne; kryminologia